HUBUNGAN STATUS VAKSINASI DENGAN KEJADIAN REINFEKSI COVID-19 PADA CIVITAS AKADEMIKA UNIVERSITAS JENDERAL SOEDIRMAN - Nara, Shaynika Rui; Rahmawati, Indah; Fatchurohmah, Wiwiek (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Backgrounds: Covid-19 reinfection occurs when someone who has experienced Covid-19 and is declared cured but is re-infected with a positive result on the PCR test with a period between the first and second infection > 90 days. This event is related to the body's immune response which is influenced by vaccine administration. Therefore, further studies need to be conducted to see the relevance between vaccination status and the incidence of Covid-19 reinfection. Objective: Knowing the relationship between vaccine status and the incidence of Covid-19 reinfection in the academic community of Jenderal Soedirman University. Method: An Analytical observational research with cross-sectional approach. The number of respondents in this study was 154 respondents. This study used a questionnaire in the form of google form as a data collection tool. Data were processed using a correlation test, the Chi-Square test to see the relationship between variables. Results: The results of this study showed that the incidence of reinfection found was 14.9%. The vaccination status of respondents at the time of Covid-19 reinfection who had not been vaccinated was 8.6%, half dose vaccine was 17.4% and full dose vaccine was 74%. The results of the Chi-square test between vaccination status and the incidence of reinfection indicate that there is no significant relationship (p-value > 0,05). Conclusion: There is no relationship between vaccine status and the incidence of Covid-19 reinfection in the academic community of Jenderal Soedirman University.